2017
DOI: 10.1159/000475878
|View full text |Cite
|
Sign up to set email alerts
|

Sweet’s Syndrome Successfully Treated with Granulocyte and Monocyte Adsorption Apheresis

Abstract: Sweet’s syndrome is a neutrophilic dermatosis characterized by an abrupt onset of painful erythematous lesions showing neutrophilic infiltrates in the dermis. Fever and an elevated neutrophil level are generally observed. Sweet’s syndrome may be idiopathic, malignancy-associated, or drug-induced (mainly involving granulocyte colony-stimulating factor (G-CSF) administration). Although systemic corticosteroids are usually effective, the symptoms of Sweet’s syndrome recur in some refractory cases. Herein, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…With advances in our understanding of the pathophysiology of neutrophilic dermatoses, especially the role of TNF-α and IL-1β, the use of targeted therapy with IL-1 and TNF-α inhibitors has been effective ( 323 , 593 , 597 – 603 ). There have been reports of several novel treatments for SS, including granulocyte and monocyte adsorption apheresis, but due to the rarity of SS and the effectiveness of established treatments there have been limited investigations into these alternative treatments ( 604 ).…”
Section: Treatment Approachesmentioning
confidence: 99%
“…With advances in our understanding of the pathophysiology of neutrophilic dermatoses, especially the role of TNF-α and IL-1β, the use of targeted therapy with IL-1 and TNF-α inhibitors has been effective ( 323 , 593 , 597 – 603 ). There have been reports of several novel treatments for SS, including granulocyte and monocyte adsorption apheresis, but due to the rarity of SS and the effectiveness of established treatments there have been limited investigations into these alternative treatments ( 604 ).…”
Section: Treatment Approachesmentioning
confidence: 99%
“…According to the literature, in patients with a refractory form of the syndrome, treatment with potassium iodide, colchicine, indomethacin, clofazimine, cyclosporine, and dapsone has also been used successfully (10). Recently, a patient with this syndrome was successfully treated with granulocyte and monocyte adsorption apheresis (14). After treatment or spontaneous remission, depending on the underlying disease, the syndrome usually has a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…GMA may be a useful non-pharmacologic tool for SS, with no safety concerns. Fujii et al (75) reported a case of a 55-year-old woman affected by SS, previously treated with PSL, nonsteroidal anti-inflammatory drugs (NSAIDs) and colchicine, who underwent GMA for three times, once a (76). At present, AOSD therapeutic strategy aims to prevent organ damage and life-threatening complications and minimize adverse effects of treatment.…”
Section: Application Of Gma In Neutrophilic Dermatosesmentioning
confidence: 99%